An Updated Checklist of the Sicilian Native Edible Plants: Preserving the Traditional Ecological Knowledge of Century-Old Agro-Pastoral Landscapes - Pasta, Salvatore; La Rosa, Alfonso; Garfì, Giuseppe; Marcenò, Corrado; Gristina, Alessandro Silvestre; Carimi, Francesco; Guarino, Riccardo (Frontiers in Plant Science, 2020)
The traditional use of native wild food plants (NWFP) may represent a valuable supplementary food source for the present and future generations. In Sicily, the use of wild plants in the human diet dates back to very ancient times and still plays an important role in some rural communities. Moreover, in this regard, the natural and cultural inheritance of this island is wealthy and diversified for several reasons. First, Sicily hosts a rich vascular flora, with 3,000 native and 350 endemic plants. Second, due to its central position in the Mediterranean, the island has acted as a veritable melting pot for the ethnobotanical knowledge of the rural communities of the entire basin. We reviewed all the available literature and, starting from such omnicomprehensive checklist, we critically revised the whole species list, basing our review on field data issuing from interviews and on our expert knowledge. As a result, we provide a substantially updated list of 292 NWFP growing on the island. Further 34 species, reported as NWFP on previous papers were discarded because they are not native to Sicily, while 45 species were listed separately because their identity, occurrence and local use as food is doubtful and needs to be further investigated. Moreover, we tried to shed light on the ecology (growth form and preferential habitat) of the Sicilian NWFP, with special focus on crop wild relatives (CWR). Our preliminary ecological analyses point out that a high percentage of these plants are linked with the so-called ‘cultural’ landscapes, patchy semi-natural environments rich in ecotones, leading to the conclusion that the maintenance of century-old agro-pastoral practices may represent an effective way to preserve the local heritage of edible plants. Our study allowed to identify as much as 102 taxa of agronomic interest which could be tested as novel crops in order to face ongoing global changes and to comply with sustainable agriculture policies. Among them, 39 taxa show promising traits in terms of tolerance to one or more environmental stress factors, while 55 more are considered CWR and/or can be easily cultivated and/or show high productivity/yield potential.